2012
DOI: 10.1167/12.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning of motion discrimination by mental imagery

Abstract: Perceptual learning can occur when stimuli are only imagined, i.e., without proper stimulus presentation. For example, perceptual learning improved bisection discrimination when only the two outer lines of the bisection stimulus were presented and the central line had to be imagined. Performance improved also with other static stimuli. In non-learning imagery experiments, imagining static stimuli is different from imagining motion stimuli. We hypothesized that those differences also affect imagery perceptual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
12
1
1
Order By: Relevance
“…For example, we can discover a new figure when we rotate a previously seen image in our mind. However, such discoveries are not “really” new but just new “interpretations.” In two recent publications, we have shown that mental imagery can lead to perceptual learning (Tartaglia et al, 2009 , 2012 ). Observers imagined the central line of a bisection stimulus for thousands of trials.…”
mentioning
confidence: 88%
“…For example, we can discover a new figure when we rotate a previously seen image in our mind. However, such discoveries are not “really” new but just new “interpretations.” In two recent publications, we have shown that mental imagery can lead to perceptual learning (Tartaglia et al, 2009 , 2012 ). Observers imagined the central line of a bisection stimulus for thousands of trials.…”
mentioning
confidence: 88%
“…Recent studies have demonstrated that perceptual learning is even possible without the presentation of stimuli ( Figure 5C). Instead, training is performed using only imaginary stimuli [22]: subjects were asked to imagine the inner part of a bisection stimulus as being offset either to the left or to the right while only the two outer lines were presented; after this form of 'training', the performance of subjects improved, as typically observed with real bisection stimuli. Imagery training has similarly been shown to improve motion-direction discrimination [23].…”
Section: Learning Without Sensory Stimulationmentioning
confidence: 99%
“…As discussed below, recent data have suggested that even sensory stimulation may be dispensable for the induction of plasticity in perceptual processes [5,22,23]; these data challenge our understanding of plasticity and learning.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research from the last decades has shown that perceptual abilities are modifiable through training and practicing 1 – 3 . While the classical method to induce perceptual learning consists of deliberately practicing a perceptual task, novel approaches were discovered in recent years that could induce comparable perceptual gains, including learning by neurofeedback 4 , mental imagery 5 , 6 , repetitive transcranial magnetic stimulation 7 9 , direct-current stimulation 10 , random-noise stimulation 11 13 , or task-irrelevant perceptual learning 14 . Furthermore, combining factors known to facilitate perceptual learning can increase its efficacy 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%